Colonial Transformations - Bach, R. author. aut Link
XIV, 290 p.
Keywords: Colonial Transformations covers early modern English poetry and plays, Gaelic poetry, and a wide range of English colonial propaganda. In the book, Bach contends that England's colonial ambitions surface in all of its literary texts. Those texts played multiple roles in England's colonial expansions and emerging imperialism. Those roles included publicizing colonial efforts, defining some people as white and some as barbarians, constituting enduring stereotypes of native people, and resisting official versions of colonial encounters.